Exact Jackson - Stechkin-type inequalities for 2π -periodic functions in L 2 and widths of some classes of functions - Shabozov, M. Sh. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We consider the problem of finding exact inequalities for the best approximations of periodical differentiablefunctions by trigonometric polynomials and the m -order moduli of continuity in the space L 2 and presenttheir applications. For some classes of functions defined by the indicated moduli of continuity, we calculatethe exact values of n-widths in the space L 2 .